Dominant atmospheric pollutants in malaysia - S. C. Poh; C. P. Tso (ASEAN Journal on Science and Technology for Development, 1985)
This Article presents a  Brief of the various types of Pollutants that are contributing to the problem of air pollution in Malaysia, As well as the mention of some episodes in air pollution that have given rise to concern here